The Correlation between Metacognitive Listening Strategies and Listening Comprehension among Students in Secondary School - Faradisa, Fani Miftakhul (RETAIN, 2021)
In learning a foreign language, listening is an essential skill to support students’ input and language development. The students use their listening comprehension in processing the input that they heard. However, many problems arise in listening comprehension. Metacognitive listening strategies is one of listening strategies that can help students to control their learning and solve problems to achieve the learning outcomes. Focusing on metacognitive listening strategies, this study was conducted to find out the correlation between metacognitive listening strategies and listening comprehension in secondary school. In order to study this relationship, 65 students were chosen as the sample of this study and were surveyed with a questionnaire and listening test. Those are Listening Comprehension Strategy Questionnaire (LCSQ) and Practice Test for the TOEFL junior standard test to determine students’ listening comprehension score. The result of this study showed that the students were more likely to use planning strategy (M= 3.78) and problem solving strategy (M= 3.72) to ease them in listening comprehension. It was found that metacognitive listening strategy had a low positive relationship with students’ listening comprehension (p= 0.024 and r= .280). The result also revealed that there was a low positive correlation between one of the component in metacognitive listening strategies, problem-solving strategy and students’ listening comprehension (p= 0.006 and r= .337). Thus, metacognitive listening strategies were beneficial for students in listening comprehension. Keywords: Listening comprehension, Metacognitive listening strategies.